Peritoneal Dialysis Catheter Placement: Percutaneous and Peritoneoscopic Techniques - El Khudari, Husameddin; Abdel-Aal, Ahmed Kamel; Abaza, Masa; Almehmi, Sloan E.; Sachdeva, Bharat; Almehmi, Ammar (Seminars in Interventional Radiology, 2022)
Chronic peritoneal dialysis (PD) is an underutilized renal replacement therapy in treating end-stage renal disease that has several advantages over hemodialysis. The success of continuous ambulatory PD is largely dependent on a functional long-term access to the peritoneal cavity. Several methods have been developed to place the PD catheter using both surgical and percutaneous techniques. The purpose of this article is to describe the percutaneous techniques using fluoroscopy guidance and peritoneoscope method. While fluoroscopic method uses fluoroscopy guidance and a guidewire to place the PD catheter, the peritoneoscopic technique utilizes a needlescope to directly visualize the peritoneal space to avoid adhesions and omentum during catheter placement. These percutaneous approaches are minimally invasive procedures that can be performed on an outpatient basis without the need for general anesthesia.
Keywords: peritoneal; dialysis; renal failure; percutaneous; image-guided; interventional; peritoneoscopic; interventional radiology